Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development sector in the past decade is partly a response to the complex and interconnected challenges facing many developing countries, including the impacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, economic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governments to experiment with different entry points and to adapt or change course when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen systems of planning and delivery for adaptation to climate change in South Asia. As the programme draws to a close, this Learning Paper reflects on some of the major lessons learnt on the challenges and opportunities of using an adaptive programme management approach to support governments to adapt to climate change. The authors are members of the ACT implementation team, representing the management, operational and technical teams, from across different locations. The paper therefore reflects their first-hand account of the reality of implementing adaptive programmes. The paper sets out a framework for the essential ingredients of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and learning; and stakeholder alignment. It also includes two sets of essential resources required: management flexibility and adequate financial resources. The paper then provides learning from ACT on how to operationalise these core principles and mobilise the necessary resources. It gives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, as well as retrospective reflections of additional actions the programme could have taken. A set of case studies unpacks how adaptive programme management has been operationalised in practice in particular locations. The authors are confident that the impact ACT has had owes in large part to it being an adaptive programme. The programme’s flexibility, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerged and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT has faced as an adaptively managed programme. The paper therefore concludes with a set of lessons learnt from ACT for the benefit of others designing and delivering adaptive programmes on climate change and other issues.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (USAID LEARN, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

How We Model Matters: A Manifesto for the Next Generation of Program Theorizing - Whynot, Jane; Lemire, Sebastian; Montague, Steve (Canadian Journal of Program Evaluation, 2019)
In this concluding article, grounded on the exemplary contributions contained in the preceding pages, the guest editors scale the proverbial soapbox and present a manifesto to guide the pursuit and advancement of the next generation of program theorizing. Formulating ten declarations for program theory development and examination, the modest hope of the authors is to motivate and inspire reflective evaluation practitioners to broaden their views, approaches, and techniques for future program theorizing.